Genetic polymorphisms of CYP3A4 among Chinese patients with steroid-induced osteonecrosis of the femoral head - Wang, Yuan (Medicine (Baltimore), 2016)
BACKGROUND: Steroid therapy has been an important reason of nontraumatic osteonecrosis of the femoral head (ONFH). Steroids are metabolized by hepatic cytochrome P4503A, a low endogenous activity of this enzyme can contribute to the pathogenesis of ONFH. The aim of this study was to investigate the associations of polymorphisms of cytochrome P4503A4 (CYP3A4) gene with steroid-induced ONFH in Chinese patients. METHODS: A total of 150 steroid-induced ONFH patients and 250 healthy controls were enrolled. We evaluated 5 single-nucleotide polymorphisms of the CYP3A4 gene in this case–control study. RESULTS: We identified rs2242480 in the CYP3A4 gene that was potentially associated with an increased risk of steroid-induced ONFH in the allele model (P = 0.023; odds ratio [OR]: 1.47; 95% confidence intervals [CI]: 1.05–2.04) and in the additive model (P = 0.028; OR: 1.44; 95% CI: 1.04–1.99) adjusted age + gender. Furthermore, we also observed a protective effect of haplotype “TG” (P = 0.025; OR: 0.69; 95% CI: 0.49–0.96) and a risk effect of haplotype “CG” (P = 0.006; OR: 1.81; 95% CI: 1.19–2.77) of the CYP3A4 gene adjusted age + gender. CONCLUSION: These findings suggested that polymorphisms of CYP3A4 gene may be associated with susceptibility to steroid-induced ONFH.